Reliance of Suku Anak Dalam to Harapan Rainforest, Indonesia: foodstuff collection preference. (2015) - David, Wahyudi; Widianingsih, Nayu Nuringdati; Ardiansyah,; Ploeger, Angelika
This study was aimed to investigate foodstuff collection pattern of Suku Anak Dalam (SAD) based on their accessibility in Harapan Rainforest (HRF) Sumatra, Indonesia. The qualitative and quantitative information was collected from three groups of SAD which consist of 34 households using semi-structured questionnaires. The research observes daily foodstuff collection; hunting/collecting, cultivating/raising and buying. Data was analysed using SPSS and MS Excel to determine the attribute that might point out SAD preference in collecting their foodstuff. SAD in all groups prefers to buy carbohydrate based food (rice) from the nearest vendor, meanwhile for protein-based food mostly depends on fish and egg; they prefer fishing and raising chicken to gain eggs. SAD in all groups have backyard garden and cultivate vegetables, and the modern group often buy vegetable for their daily consumption. Most of food items could be found in the forest, and only rice and spices are imported from elsewhere.